Implementasi Media Jersey Berangka dalam Meningkatkan Hasil Belajar Pada Materi Mengurutkan Bilangan di SDN 02 Rowoyoso Kabupaten Pekalongan - Luthfiyah Luthfiyah; Tiara Fadhilah; Barotut Taqiyah (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2024)
This research was conducted to improve learning outcomes on number sorting material using numerical jersey media in grade II SDN 02 Rowoyoso. This study uses a class action research method that uses II cycles in which each cycle consists of planning, implementing, observing, and reflecting activities. The data collection techniques used are observation, tests, and documentation. The results of classroom action research found that numerical jersey media can improve student learning outcomes. In the first cycle student learning outcomes were 55.55% (10 students who completed) and 44.44% (8 students who were not completed). While in cycle II student learning outcomes increased to 86.66% (13 students who completed) and 27.77% (5 students who have not completed). So it can be concluded that students experience improved learning outcomes and achieve the minimum completeness criteria determined.